Potencialidades do uso de aplicativos móveis no compartilhamento de estratégias contemplando à atuação profissional docente - Tiecher, Sergio Reni (2020)
This study, linked to the research line Development of Educational Network Technologies, of the Graduate Program in Educational Network Technologies - PPGTER, Professional Master's Degree, from the Federal University of Santa Maria-UFSM, started from the following research problem: How creation of a mobile application for the sharing of educational units among teaching professionals contribute to the development of strategies and practices to be used in the classroom ?. The general objective of the study was to understand how mobile learning, through educational applications, promotes the development and sharing of methodologies used in school environments. Specifically, we sought to: 1) Understand how mobile learning is inserted in the context of content sharing for professional education in this environment; 2) Analyze in the current repositories, the potential of mobile applications that perform this function or not specifically among teaching professionals; 3) Develop and describe how a mobile application can contemplate the creation of proposals for the development of educational menus for professionals. As a result, the master's product consists in the development of an application for mobile devices, based on the use of network technologies in technical education, promoting content sharing processes. In addition, it emphasizes the exchange of teaching practices among these professionals, allowing the product to be used in the classroom. The theoretical framework provides information related to educational technologies, mobile learning, and the use of mobile devices in the school space. The proposed methodology was an applied, qualitative study, following the design of the data collection research. The participant approach, as well as the questionnaire made available, are the instruments adopted in the production and development of the tool of this study, which had as target audience 20 teachers of Technical Education. The research was carried out by means of pedagogical elements linked to networked educational technologies, especially mobile learning. The approach used considers that there is a gap regarding the action of the researchers and the analyzed group, at different times of the work. Thus, this study was organized into categories, each with steps to plan, develop, implement, execute, analyze and reflect on the mobile learning process. Content analysis and evaluation was used to show the data, which pointed out the categories of the tool: usability, interaction and sharing of actions. As a result, it is expected that teaching professionals use the tool in promoting pedagogical strategies based on the process of creating these spaces in mobile environments. As a final result, it was noticed that when using the tool to inspire the production of study units, some research subjects shared their own creative work within that same space. This proactive and collaborative aspect demonstrates effective mobile learning among the professionals involved who used the tool.